The Impact of Artificial Intelligence on International Marketing Strategies - Borovik, Sofiia (2025)
This thesis examines how artificial intelligence (AI) influences the efficiency and effectiveness of international marketing strategies. The main objectives are to analyze the role and impact of AI in international marketing, explore its main benefits and challenges, and provide actionable recommendations for companies. Using qualitative research, the study combines a case analysis of Amazon, small-scale business use cases, and expert interviews to investigate AI’s role in core marketing areas such as marketing research, segmentation and targeting, positioning, content creation, and customer service. The findings show that AI significantly enhances the above-mentioned areas, leading to higher customer engagement, sales, and overall profitability. However, it also introduces challenges such as data security risks, algorithmic bias, hallucinations, emotional superficiality of AI, infrastructure demands, and sustainability concerns. Based on these insights, the thesis provides practical recommendations for companies aiming to integrate AI effectively into global marketing strategies.